Fetal Fibronectin (fFN) on the Imminent Premature Parturition in Correlation with Incidence of Preterm Labor - Keman, Kusnarman; Nugrahanti, Prasetyorini; Supriany, Ni Wayan (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To determine the relationship of fFn levels in cervicovaginal discharge of pregnant women who experience imminent premature parturition with the incidence of preterm labor. Method: The study was carried out with Analytic Observational Prospective Cohort using cervicovaginal discharge of pregnant women that experienced imminent premature parturition taken from the delivery room of Obstetrics and Gynecology department dr. Saiful Anwar Hospital, Malang as well as Bangil Hospital and Ngudi Waluyo Wlingi Hospital. Statistical analysis was performed using the Shapiro-Wilk test and comparison test used independent samples t test for normal data, Mann-Whitney test if not. All analysis used SPSS for Windows 19.0 software. Result: Thirty two patient samples was examined, 14 patients (43.75%) were primigravida and 18 patients (52.56%) is multigravida. 17 of these patients (53.13%) experienced aterm labor and 15 patients (46.87%) experienced preterm labor. Mann-Whitney test of the mean fFN levels between the aterm group (13.01 ± 7.57 ng/ml) and the preterm group (56.29 ± 27.77 ng/ml) showed a significant difference (p-value = 0.000 > 0.05). Moreover, Spearman’s Rho correlation test also showed a strong correlation between fFN level and incidence of preterm labor (R = 0.797, p < 0.05). Conclusion: fFN levels is significantly increase in cervicovaginal discharge from pregnant women with imminent premature parturition who experience preterm labor than pregnant women who experience aterm labor. Therefore, this result suggests that fFN has potential ability to become useful modality in preterm labor diagnosis. [Indones J Obstet Gynecol 2016; 1: 8-14] Keywords: cervicovaginal discharge, fFN, imminent premature parturition, preterm labor